2016
DOI: 10.1155/2016/6218659
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Accuracy of Angular Measurements on Laser Scanning Created 3D Models of Dry Skulls

Abstract: The aim of the study was to assess the accuracy and reliability of skull angles measured on 3D models created by laser scanning. Five skulls were measured through both conventional and digital measuring methods. The 3D models were created using a hand-held laser scanner Creaform VIUscan™. Seven angular characteristics were measured three times by two observers. The intra- and interobserver reliability were assessed using intraclass correlation coefficient. The differences between the digital and direct measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In spite of the high variability of the landmarks which constructed it, the deviation of the FH does not exceed 0.5°, which indicates that this plane could be used as a stable landmark‐based reference plane in models obtained with different resolutions. The FH has also been previously reported as sufficiently stable and appropriate for different treatments and studies (Daboul et al, ; Toneva et al, ). Based on the mean MEs and ranks in our study, the most imprecise landmark from those constructing FH is porion (R).…”
Section: Discussionmentioning
confidence: 81%
“…In spite of the high variability of the landmarks which constructed it, the deviation of the FH does not exceed 0.5°, which indicates that this plane could be used as a stable landmark‐based reference plane in models obtained with different resolutions. The FH has also been previously reported as sufficiently stable and appropriate for different treatments and studies (Daboul et al, ; Toneva et al, ). Based on the mean MEs and ranks in our study, the most imprecise landmark from those constructing FH is porion (R).…”
Section: Discussionmentioning
confidence: 81%
“…According to this study, all measurements exhibited an acceptable measurement error indicating high repeatability and precision, whereas their respective R coefficients demonstrated that all measurements may be regarded as reliable. These findings are in agreement with those reported by Toneva et al (2016). Furthermore, most of the measurements are below the intraand inter-observer %TEM thresholds of 1% and 1.5%, respectively, which are usually considered acceptable for skillful anthropometrists .…”
Section: Discussionsupporting
confidence: 92%
“…Most often studies on landmark digitization error rely on repetitive measurements over a very small sample for assessing accuracy and repeatability Tallman et al 2014;Toneva et al 2016;Toneva et al 2017). Apart from the intrinsic precision and accuracy of every measuring equipment, landmark digitization error has two fundamental contributors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of metric characteristics of digitally created 3D reconstructions of anatomical structures has been previously studied. It has been proved that linear and angular measurements of 3D models based on both laser scanning and CT scans are reliable and accurately correspond to the original bones [13, 2931]. Following these conclusions, it can be believed that an object printed on the base of 3D digital reconstruction should also ideally depict the original.…”
Section: Discussionmentioning
confidence: 99%